2023
DOI: 10.3389/ti.2023.11506
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Power Density Predicts Prolonged Ventilation Following Double Lung Transplantation

Alessandro Ghiani,
Nikolaus Kneidinger,
Claus Neurohr
et al.

Abstract: Prolonged mechanical ventilation (PMV) after lung transplantation poses several risks, including higher tracheostomy rates and increased in-hospital mortality. Mechanical power (MP) of artificial ventilation unifies the ventilatory variables that determine gas exchange and may be related to allograft function following transplant, affecting ventilator weaning. We retrospectively analyzed consecutive double lung transplant recipients at a national transplant center, ventilated through endotracheal tubes upon IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…This index incorporates respiratory rate and airway pressures, factors that also have been independently associated with weaning failure in the recent multicenter WEAN SAFE study 21 . MP density has also been shown to be an accurate predictor of prolonged ventilation after double lung transplantation, with LTC dyn -MP demonstrating the strongest correlation with invasive ventilation time following a patient’s transfer from the operating room to the ICU 22 . However, further research is required as other studies have demonstrated conflicting findings 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This index incorporates respiratory rate and airway pressures, factors that also have been independently associated with weaning failure in the recent multicenter WEAN SAFE study 21 . MP density has also been shown to be an accurate predictor of prolonged ventilation after double lung transplantation, with LTC dyn -MP demonstrating the strongest correlation with invasive ventilation time following a patient’s transfer from the operating room to the ICU 22 . However, further research is required as other studies have demonstrated conflicting findings 23 .…”
Section: Discussionmentioning
confidence: 99%